The Effectiveness of Microsite-Based Learning Media to Enhance Students’ Understanding of Matrix Concepts at Sekolah Indonesia Kuala Lumpur - Fauzan Putra Afandi; Lisanul Uswah Sadieda; Dewi Mariani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study was motivated by the low level of students’ understanding of matrix concepts, which is largely caused by conventional teaching methods that lack interactivity and visual support. To address this issue, a microsite-based learning medium was developed to present matrix material in an interactive and visually supported manner. The study aimed to examine the effectiveness of using a microsite to improve the conceptual understanding of eleventh-grade students at the Indonesian School of Kuala Lumpur. A quasi-experimental method with a pretest–posttest control group design was employed involving 33 students, consisting of 20 students in the experimental group and 13 students in the control group. The experimental group received microsite-based instruction, while the control group was taught using conventional methods. The research instrument was an essay test developed based on Kilpatrick’s indicators of conceptual understanding.The results showed that the experimental group achieved a mean gain of 81.46, whereas the control group obtained a mean gain of 74. Students in the experimental group demonstrated consistently high performance across most conceptual understanding indicators, while the control group showed moderate understanding with weaknesses in higher-order indicators, particularly in applying concepts across multiple representations. The Mann–Whitney U test indicated a significance value of 0.001, which is lower than 0.05, with an effect size of 0.573 categorized as large.These findings confirm that microsite-based learning is more effective than conventional instruction in enhancing students’ conceptual understanding of matrix material.